Hexane extract from Lindera communis roots: wound healing properties and membrane-disruptive activities against methicillin-resistant Staphylococcus aureus - Miaomiao Wang; Miaomiao Wang; Miaomiao Wang; Xian Hu; Xian Hu; Xian Hu; Liya Liu; Liya Liu; Liya Liu; Liya Liu; Yi Zhong; Yi Zhong; et al. (Frontiers in Pharmacology)
IntroductionThe extensively used Lindera communis Hemsl. (Lauraceae) in traditional Chinese medicine has been specifically employed for wound healing and treating skin diseases in cattle and horses, suggesting its potential antibacterial properties. To explore the antibacterial activities of L. communis plants, we investigated the chemicals, antibacterial activities and wound healing and of the n-hexane fraction of L. communis roots (LCH).MethodsOur study included detecting phytochemical constituents, determining minimum inhibitory concentration (MIC) for different extract fractions, analyzing growth curves, assessing membrane integrity, monitoring potential changes in the membrane using scanning electron microscopy, and evaluating wound healing in rat excisional wounds.ResultsBased on our findings, humulene-type sesquiterpenes, guaiane-type sesquiterpenes, and lauric acid were identified from the LCH, responsible for antibacterial and wound healing activities. The results are that LCH affected the growth of methicillin-resistant Staphylococcus aureus (MIC: 0.1 mg/mL) through morphological alterations and disrupting cell surface structures, causing membrane hyperpolarization and altering membrane integrity. This result was subsequently validated through SEM analysis and cytotoxicity against HaCaT cells (IC50 1.83 ± 0.21 mg/mL). LCH also has exhibited remarkable effectiveness in healing rat excisional wounds, reinforcing its traditional use as a wound-healing agent.DiscussionThe findings substantiate the scientific essence of traditional applications, while also exhibiting significant potential as a promising candidate for the development of innovative and readily accessible wound healing agents.